ON RAY JOHNSON'S SEXUALITY, LOVES, AND FRIENDSHIPS: an interview between william s. wilson and benjamin kahan. Issue 1 (2nd January 2018) - Kahan, Benjamin
Abstract: This interview was conducted with one of the closest friends of the visual artist Ray Johnson, the late photographer and writer William S. Wilson. Johnson was a fixture of the New York downtown art scene in the late 1940, 1950s, and 1960s. He was influenced by Abstract Expressionists and Pop artists alike, but was a true original, widely considered to be the founder of "mail art" and also an important collagist and performance artist. Wilson helped Johnson to formulate the idea of "mail art" as they exchanged correspondence, thoughts, ideas, experiences, and much else besides. In this interview, Wilson discusses Johnson's sexuality, sadomasochistic practice, and philosophy of friendship. He provides hitherto unknown details about Johnson's intimate relations with the artist Richard Lippold and life at Black Mountain College (one of the leading centers of the mid-twentieth-century literary and artistic avant-garde). Wilson also recounts details of Johnson's relation to women in terms of art, friendship, love, and sex. But more than anything, this interview captures the atmosphere of queer life in the middle decades of the twentieth century and Johnson's particular experiences of that era.